A compact four‐element MIMO antenna for WLAN applications. Issue 2 (10th January 2018) - Pandit, Soumen; Mohan, Akhilesh; Ray, Priyadip
Abstract: This article presents a compact four‐element multiple‐input multiple‐output (MIMO) antenna for wireless local area network applications. The overall volume of the proposed MIMO antenna is 26 mm × 26 mm × 0.8 mm and the edge‐to‐edge distance is 4 mm. The MIMO antenna operates at 5.6 to 5.8 GHz frequency band with isolation greater than 15.4 dB. The envelope correlation coefficient and the channel capacity loss for the proposed MIMO antenna are within the acceptable limits in the operating frequency band. The simulated results are verified with fabrication and measurements.